The role of reoperation after recurrence of Cushing's disease. Issue 2 (March 2021) - Cardinal, Tyler; Zada, Gabriel; Carmichael, John D.
Abstract : Surgical failure or recurrence of Cushing's disease can be treated with medical therapy, radiotherapy, adrenalectomy, and/or repeat transsphenoidal surgery, all of which have their respective benefits and drawbacks. Redo transsphenoidal surgery has been shown to achieve at least short-term remission in about 40–80% of patients and is associated with low rates of morbidity and near-zero mortality, albeit higher rates of postoperative hypopituitarism, diabetes insipidus, and cerebrospinal fluid leak than initial resection. Despite this, recurrence may ensue in 50% of patients. When selecting patient candidates for reoperation, many predictors of postoperative outcomes have been proposed including imaging characteristics, histopathological staining, intraoperative tumor visualization, and tumor size, however no single predictor consistently predicts outcomes. Redo transsphenoidal surgery should be performed by an experienced pituitary surgeon and patients should be followed at a tertiary care center by a multidisciplinary team consisting of an experienced endocrinologist and neurosurgeon to monitor closely for remission and recurrence.